2011
DOI: 10.1186/1756-0500-4-192
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced tuberculosis case detection among substitution treatment patients: a randomized controlled trial

Abstract: BackgroundHistorically, HIV, TB (tuberculosis) and illegal drug treatment services in Estonia have been developed as vertical structures. Related health care services are often provided by different health care institutions and in different locations. This may present obstacles for vulnerable groups, such as injecting drug users (IDU), to access the needed services. We conducted a small scale randomized controlled trial to evaluate a case management intervention aimed at increasing TB screening and treatment e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…The reason for higher LTBI prevalence in the Canadian studies might be related to the use of lower TST cut-off of 5 mm, regardless of the HIV status. Utilizing interferon gamma release assay (IGRA), a survey in Estonia reported a very low LTBI prevalence (7.4%) among MMT attendees (Ruutel et al, 2011), while a similar report from the United States showed higher prevalence (34%) of IGRA positivity among crack cocaine smokers in Texas (Grimes, Hwang, Williams, Austin, & Graviss, 2007). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reason for higher LTBI prevalence in the Canadian studies might be related to the use of lower TST cut-off of 5 mm, regardless of the HIV status. Utilizing interferon gamma release assay (IGRA), a survey in Estonia reported a very low LTBI prevalence (7.4%) among MMT attendees (Ruutel et al, 2011), while a similar report from the United States showed higher prevalence (34%) of IGRA positivity among crack cocaine smokers in Texas (Grimes, Hwang, Williams, Austin, & Graviss, 2007). …”
Section: Discussionmentioning
confidence: 99%
“…These programs provide a large population of PWID or PWUD with access to HIV care, utilizing the expertise of drug treatment staff in serving this population (Rothman et al, 2007). Despite the potential synergistic impact of addressing multiple co-morbidities, many countries challenged with the syndemic of HIV, TB and substance use frequently develop uncoordinated vertical programs, which are managed separately at the local and national levels (Ruutel et al, 2011; Sylla et al, 2007). Additionally, the provision of effective management and interventions of multiple co-morbidities for PWUD have been complicated by multi-level barriers to accessing health services and reciprocal mistrust between PWUD and conventional health care providers (Altice, Kamarulzaman, Soriano, Schechter & Friedland, 2010; Rothman et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…14 Case-finding studies for TB in methadone clinics have not previously been performed in Africa; however, they have been performed elsewhere. 1620 Selwyn et al examined rates of TB activation among HIV-infected drug users on methadone in New York City, NY, USA, and found that 4% of individuals who were purified protein derivative positive later developed active TB. 17 Another study that screened 112 methadone patients in Estonia found no active cases of TB.…”
Section: Discussionmentioning
confidence: 99%
“…However, none of these projects had parallel control groups, and instead were compared with routinely collected data from the year before. Hossain 2010 No parallel control group Kaboru 2013 No parallel control group Kakinda 2016 No parallel control group Khan 2007 No intervention to increase TB diagnosis Kuznetsov 2014 No parallel control group Lebina 2016 No parallel control group Ntinginya 2012 No parallel control group Oshi 2016 No parallel control group Prasad 2016 No parallel control group Pronyk 2001 Not a TB case‐finding study Ruutel 2011 Not a relevent comparison. This study screened intravenous drug users participating in a methadone substitution programme for TB.…”
Section: Characteristics Of Excluded Studies [Ordered By Study Id]mentioning
confidence: 99%